Analgesic Activity of a Glucan Polysaccharide Isolated from Agaricus blazei Murill. (19th September 2013) - Gonzaga, Maria Leônia C.; Menezes, Thiago M. F.; de Souza, José R. R.; Ricardo, Nágila M. P. S.; Freitas, Ana L. P.; Soares, Sandra de A.
Abstract : A water soluble polysaccharide and its selective precipitated fractions (F1, F2, and F3) were isolated from hot water extract of fruiting bodies of Agaricus blazei Murril known as Agaricus brasiliensis to evaluate the analgesic activity of the materials in Swiss mice. The isolated material and its fractions were characterized by two-dimensional COSY and HMQC spectra as β -(1→6)- α -(1→4)-glucan-bound-protein polysaccharide constituted mainly by β -(1→6) glucan. The glucan-protein polysaccharide and its fractions were analyzed in relation to the protein, carbohydrate, and mineral elements contents. The analysis of the glucan-protein complex revealed a total carbohydrate content of 36.95% and protein conjugated content of 17.24%. The mineral elements found in larger proportion were K, Na, Ca, P, and Zn. The analgesic activity bioassay of the β -(1→6)- α -(1→4)-glucan bound-protein polysaccharide and its fractions in Swiss mice indicated a significant effect.